MiR-182 promotes apoptosis of neural cells in cerebral infarction rats by PI3K/AKT signaling pathway: Role of MiR-182 in cerebral infarction - Yang, Ren; Zeng, Chen (Cellular and Molecular Biology, 2023)
To explore the effects of micro ribonucleic acid (miR)-182 on the proliferation and apoptosis of neural cells in cerebral infarction rats and its underlying mechanism. The rat model of cerebral infarction was established, and neural cells were extracted accordingly. The cell proliferation ability was detected via cell counting kit-8 (CCK8) assay. In addition, the apoptosis rate was determined through flow cytometry and the activity of active caspase-3. Furthermore, the interaction between miR-182 and PI3K was explored via dual luciferase reporter assay, and the protein expression levels were observed via Western blotting. The neural cells in mouse brain tissues significantly decreased in the model group compared with that in the control group via HE stain. Additionally, the expression level of miR-182 was significantly increased in the model group compared with that in the control group. Furthermore, overexpression of miR-182 could inhibit the proliferation of neural cells through inducing cell apoptosis. Besides, the results of the luciferase reporter assay showed that the relative luciferase activity in neural cells could be inhibited by the transfection with miR-182 (P<0.05). Overexpression of miR-182 significantly reduced the protein expression levels of phosphatidylinositol 3-hydroxy kinase (PI3K) and p-AKT. MiR-182 induces apoptosis of neural cells through inhibiting the PI3K/AKT signaling pathway, which plays an important regulatory role in the apoptosis of neural cells in cerebral infarction rats.